Editorial. Issue 2 (1st December 2019) - Abrams, Benjamin; Travaglino, Giovanni A.
Abstract : This issue of Contention is definitively international, featuring data and cases from dozens of countries including Rwanda and China. We are proud to be a journal sought out by scholars working on diverse non-Western cases as well as by those conducting ambitious international analyses. As editors, we firmly believe that an interdisciplinary journal is best served by also being international, and as the journal continues to grow, we are looking to turn our attention toward building editorial teams featuring excellent scholars from around the world. We hope that the variety of international cases in our pages will one day be mirrored by a similarly international community of authors, reviewers, and editors.